Obstetrical Outcomes of Head and Neck (Nonthyroid) Cancers: A 27-Year Retrospective Series and Literature Review - Ernesto Antonio Figueiró-Filho; Richard P. Horgan; Nidal Muhanna; Jacqueline Parrish; Jonathan C. Irish; Cynthia V. Maxwell (Thieme Medical Publishers, Inc., 2019)
Abstract Objective To describe the clinical presentation and obstetrical outcomes of nonthyroid head and neck cancers (HNCs), and to review literature on this rare condition in pregnancy. Study Design Pregnant women with nonthyroid HNC were identified retrospectively from 1990 to 2017. Maternal, neonatal, pregnancy, and demographic data were collected. A review of the literature from January 1980 to May 2018 was performed. Results Over the 27-year time period, 16 women with history of nonthyroid HNC were identified (9 diagnosed during and 7 diagnosed before current pregnancy). The cases were analyzed in detail and the most updated review of management of each type of HNC was provided. Conclusions HNCs are rare with diagnosis and management challenges during pregnancy. In this series, the cases diagnosed and managed previously to pregnancy presented better perinatal outcomes than the cases presented during pregnancy. The maternal outcomes appeared similar for HNC diagnosed before or after pregnancy.